ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PEDAGANG DI PASAR BADUNG KOTA DENPASAR - Dara Cantika Damayyanti Effendi; Ni Nyoman Yuliarmi (CV. Adiba Aisha Amira, 2025)
Traditional markets such as Badung Market in Denpasar City remain central to community economic activities. However, despite infrastructure modernization and the adoption of digital technology, income disparities among traders persist. This study aims to analyze the influence of capital, working hours, business duration, number of buyers, digital technology, and business location on traders’ income at Badung Market. The research employed a quantitative approach using multiple linear regression analysis. A total of 88 respondents were selected through stratified random sampling based on business location, with data collected through observation, structured interviews, and in-depth interviews. The results reveal that all independent variables simultaneously have a significant effect on traders’ income. Partially, the variables of capital, working hours, business duration, number of buyers, and business location exert a positive and significant influence. Conversely, digital technology shows a negative and insignificant effect. These findings indicate that although digitalization has been introduced, its utilization remains limited due to traders’ low digital literacy and constraints in technology adoption. The study highlights the importance of strengthening traditional factors such as capital and location, while also emphasizing the need for guidance in the effective use of digital technology in line with traders’ capacities.